INTERGENERATIONAL EDUCATIONAL ATTAINMENT, FAMILY CHARACTERISTICS AND CHILD OBESITY. Issue 4 (28th August 2015) - Jones, Antwan
Summary: This study used US National Longitudinal Study of Youth data to explore how exposure to different socioeconomic conditions (proxied by maternal education) before birth can shape child weight. Using endogenous selection regression models, the findings suggest that educational selectivity affects weight gain. Mothers whose mothers graduated from high school were more likely to complete high school, and mothers reared in an intact family had higher levels of education. However, mothers who had given birth as a teenager had the same educational outcomes as mothers who gave birth in their post-teenage years. Based on this intergenerational educational selectivity, caretaking (e.g. breast-feeding) was found to be associated with a lower child body mass index (BMI), while negative maternal characteristics (e.g. mothers with high BMIs) were associated with higher child BMIs. Thus, educational selectivity influences child health through values passed on to the child and the lifestyle in which the child is reared. Maternal education may be tied to parenting, which relates to child obesity risk.